Penyelesaian Sengketa Adat Mengenai Tapal Batas Antara Desa Pakraman Penatih Puri dan Desa Pakraman Peguyangan - Adi Trinaya Dewi, A.A. Mas (Jurnal Komunikasi Hukum, 2021)
Blurred village boundaries can cause confusion in the implementation of village services, pawedalan, punia funds, kasucianism and non-compliance for local residents. This condition is believed by Hindus to cause disruption of social balance (sekala) and magic (niskala). As a result of the unclear territorial boundaries of the Pakraman village, there was a customary reaction in Pakraman Penatih Puri Village with Pakraman Peguyangan Village. This research will discuss 2 (two) main points, namely: (1) How is the settlement of customary disputes regarding the boundaries between Pakraman Penatih Puri Village and Pakraman Peguyangan Village? (2) What are the factors that hinder the settlement of customary disputes regarding the boundary between Pakraman Penatih Puri and Pakraman Peguyangan villages? This type of research is qualitative research that is descriptive and analytical in nature. Settlement of customary disputes regarding the boundaries between Pakraman Penatih Puri Village and Pakraman Peguyangan Village which are resolved by means of mediation by making a collective agreement or pararem which is used as the legal basis in the Pakraman village. Awig-awig is made in order to create harmony and security in society.